2019
DOI: 10.1001/jama.2019.15720
|View full text |Cite
|
Sign up to set email alerts
|

The Point-of-Care INR Test for Vitamin K Antagonist Monitoring

Abstract: A 59-year-old man who had been taking warfarin for 16 years for recurrent deep vein thrombosis and a left ventricular thrombosis presented to the anticoagulation management service for a follow-up visit. His warfarin had been managed via point-of-care (POC) testing for the past 4 years with a goal international normalized ratio (INR) of 2.0 to 3.0. On presentation, his POC INR was 3.7. He reported no extra warfarin doses, medication changes, dietary nonadherence, or bleeding. His warfarin dosage was 36 mg/wk (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Our finding is in line with previous studies that showed a positive bias of POC INR values and the bigger systemic difference in higher INR values 10‐14 . The US Food and Drug Administration (FDA) recommends that a POC INR value >4.5 should be confirmed by laboratory analyzers, 32 and Anderson, et al 33 suggested an even lower INR cutoff of 3.5 for patients' safety. Our results cannot be extrapolated to other and newer reagents.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding is in line with previous studies that showed a positive bias of POC INR values and the bigger systemic difference in higher INR values 10‐14 . The US Food and Drug Administration (FDA) recommends that a POC INR value >4.5 should be confirmed by laboratory analyzers, 32 and Anderson, et al 33 suggested an even lower INR cutoff of 3.5 for patients' safety. Our results cannot be extrapolated to other and newer reagents.…”
Section: Discussionsupporting
confidence: 92%
“…These devices are commonly utilized in outpatient ambulatory care settings to provide therapeutic drug monitoring for patients on warfarin therapy. 8 There are also a subset of patients who may be qualified to monitor their INR from home with their own POC INR machine. The results of the HOME INR Study (THINRS) showed that patients monitoring their INR from home utilizing POC INR machines significantly increased patient satisfaction and quality of life.…”
Section: Purposementioning
confidence: 99%
“…International Normalised Ratio (INR) is a laboratory test used to check the anticoagulant effect of warfarin by using the outcome of the prothrombin time (PT) test, a measurement which monitors the time it takes blood to coagulate (Anderson, Wool and Madden, 2019). Target INR for those prescribed anticoagulants is ideally 2.5 (therapeutic range between 2-3), or 3.5 for individuals with recurrent VTE's (Keeling et al, 2011;Pavord and Webster, 2015;AAGBI, 2016;NICE, 2020).…”
Section: International Normalised Ratio (Inr)mentioning
confidence: 99%